PENINGKATAN PENGETAHUAN IBU DAN KELUARGA TENTANG FAKTOR YANG MEMPENGARUHI PRODUKSI ASI: PENINGKATAN PENGETAHUAN IBU DAN KELUARGA TENTANG FAKTOR YANG MEMPENGARUHI PRODUKSI ASI - sri mulyani; Indah Mawarti (Universitas Jambi, 2023)
The United Children’s Fund (UNICEF) and the Word Health Organitazion (WHO) recommend babies and be given Mother Milk (ASI) for at least six month. Solid food as additional food is given after the child is 6 months old, and breast milk is still given until the child is two years old. Mother's milk contains all the nutrients a baby needs during the first six months of birth. Infants aged less than six months are not recommended to be given Breast Milk Replacement (PASI), because it can increase the possibility of contamination and increase the risk of contracting disease, especially diarrhea. Breastfeeding success is influenced by several factors.This activity was held on October 8. The location of the activity was carried out at the Batik Legok House in the working area of the Putri Ayu Public Health Center, Jambi City. Participants in the activities of pregnant and lactating women who are in the working area of Pukesmas Putri Ayu, Jambi City. This activity was carried out using the group extension method. Community service activities received a good response from all participants. The number of counseling participants was 17 participants. Mother's knowledge increased after being given counseling. It is hoped that the knowledge and understanding of pregnant and lactating women regarding the factors that affect breast milk production will be beneficial in efforts to successfully provide exclusive breastfeeding for babies.